KARAKTERISASI DAN ESTIMASI EMISI GAS RUMAH KACA DARI SAMPAH PADAT KOTA DI TPA BAKUNG KOTA BANDAR LAMPUNG - dewi Agustina Iryani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Abstract. Municipal Solid Waste (MSW) which is disposed to unmanaged landfill site  generates the large quantities of greenhouse gas (GHG) called landfill gas. This Landfill gas is composed from various kind of gases, one of  those gases is Methane (CH4 ) that is 21 times more effective than carbon dioxide (CO2) which contributes to global warming. The number of methane gas generated from organic waste has different values depending on the waste characteristics. This study is aimed to calculate the GHG of Bakung landfill which is located at Bandar Lampung city by considering  about the waste characterization using various laboratory testing and the default data of IPCC Inventory software 2006. The Results showed that the landfill is able to generate an average of  2,665 m3 Million methane during 2018 – 2032.Keywords: Bakung landfill site, waste characteristic, greenhouse gas, methane